2015
DOI: 10.1080/13102818.2015.1114906
|View full text |Cite
|
Sign up to set email alerts
|

Study on enzymatic browning in suspension cultures of licorice cells

Abstract: Enzymatic browning is one of the main obstacles encountered in the establishment of suspension systems of licorice cells. Browning of cells may result in decreased viability, poor growth and even death. The present study investigated the mechanism of browning reactions and the effective controlling methods. The results showed that the cell viability and membrane permeabilization obviously changed when the cells were transferred to liquid medium. The transformation caused rapid increase in the levels of polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…In a different study, licuraside, isoliquiritin and licochalcone A derivatives isolated from G. glabra were found to have inhibitory effects on the tyrosinase activity (Dong et al, 2014). Similar results were then reported by Li et al (2016) in which the liquorice cell cultures reported to prevent browning and maintain cell viability in in vitro studies.…”
Section: Discussionsupporting
confidence: 88%
“…In a different study, licuraside, isoliquiritin and licochalcone A derivatives isolated from G. glabra were found to have inhibitory effects on the tyrosinase activity (Dong et al, 2014). Similar results were then reported by Li et al (2016) in which the liquorice cell cultures reported to prevent browning and maintain cell viability in in vitro studies.…”
Section: Discussionsupporting
confidence: 88%
“…Callus browning is formed due to the presence of phenolic compounds. The phenolic is oxidized after the cell membrane is degraded or the cells are organized, followed by chlorophyll degradation [16]. The browning process is increasing due to the influence of gamma irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Pada kondisi normal, enzim dan substrat berada di ruang yang berbeda dalam sel dan akan keluar bersama ketika sel rusak. Perubahan permeabilitas membran menyebabkan pelepasan enzim dan substrat pada sitosol dan dapat memicu pencoklatan (Li et al, 2016).…”
Section: Hasil Dan Pembahasanunclassified